2003
DOI: 10.1002/anie.200300578
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radicals in Metal‐Assisted Oxygenation Reactions

Abstract: The oxo-functionalization of organic substrates with the aid of metal oxo moieties is of fundamental importance not only in nature but also in academic and industrial research. Nevertheless the corresponding reaction mechanisms remain among the most enigmatic in chemistry and few of them are understood in detail. Recent research efforts have resulted in significantly improved information: in the cases of many oxygenation reactions evidence has been provided for the occurrence radical intermediates, even though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(99 citation statements)
references
References 281 publications
2
92
1
4
Order By: Relevance
“…The X-ray crystal-structure analysis of complex 3f with 4-unsubstituted pyridine ligands [24] revealed that the pyridine Natom is protonated and thus is not involved in any binding interaction with the iron center. However, in agreement with Bartons mechanistic scenario [31] [32], we propose that the trinuclear complex decomposes to a mononuclear species, in which the external pyridine competes with the 2,6-diacylpyridine as N-donor ligand 7 ). Even if the 4-substituent exerts some influence on the donor properties of the 2,6-diacylpyridine moiety, these effects are diluted by the large excess of pyridine solvent.…”
Section: Methodssupporting
confidence: 71%
“…The X-ray crystal-structure analysis of complex 3f with 4-unsubstituted pyridine ligands [24] revealed that the pyridine Natom is protonated and thus is not involved in any binding interaction with the iron center. However, in agreement with Bartons mechanistic scenario [31] [32], we propose that the trinuclear complex decomposes to a mononuclear species, in which the external pyridine competes with the 2,6-diacylpyridine as N-donor ligand 7 ). Even if the 4-substituent exerts some influence on the donor properties of the 2,6-diacylpyridine moiety, these effects are diluted by the large excess of pyridine solvent.…”
Section: Methodssupporting
confidence: 71%
“…Because of favorable combinations of covalency and oxidation/reduction potentials, the activation of molecular oxygen by its coordination to one or two supported ͑i.e., ligated͒ Cu͑I͒ ions is common to a number of biological and inorganic catalytic processes. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] In the case of monocopper species LCuO 2 , where L is a general ligand or ligands, one possible oxidation state that may be assigned to the complex is LCu͑II͒O 2 ͑−͒; thus, the copper atom has been oxidized by one electron and the O 2 fragment is formally a superoxide radical anion. Similarly, in the case of dicopper species ͑LCu͒ 2 O 2 , one possible oxidation state of the complex is formally ͓LCu͑II͔͒ 2 ͓͑O 2 ͒͑2−͔͒; in this instance, each copper atom has been oxidized by one electron and the O 2 fragment is formally a peroxide dianion.…”
Section: Application To Supported Cuo 2 and Cu 2 O 2 Systemsmentioning
confidence: 99%
“…In many cases, organic reactions occur with the formation of free carbon-and oxygen-centered radicals [243][244][245][246], and alkyl hydroperoxides are formed. A few tests can be used to detect the formation of ROOH from RH.…”
Section: Mechanism Of Oxidation By Peroxides: Radical or Not Radicalmentioning
confidence: 99%